SISTEM KONTRAK PENGOLAHAN LIMBAH PADAT RUMAH SAKIT PEMERINTAH - Maulana, Muchsin; Kusnanto, Hari; Suwarni, Agus (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2015)
AbstractBackground: Jogja Hospital is a Government-owned Hospital run by the Government of city of Jogyakarta. In its daily activities, the hospital produces waste which, if not properly discharged or burned, may cause adverse effect on workers as well as the surrounding area. Jogja hospital has Incinerator, thus simplifying the management such waste. The waste management including the rules, procedures and policymaking need to be explored to investigate the process of waste management of Jogja hospital. Methods: This study used a qualitative descriptive case study in order to get a clear picture or description about certain situation objectively. The unit analysis was the solid waste management in the Jogja Hospital. In-depth interviews were conducted with the Head of Environmental Health Installation and Waste Management Officer. Data were obtained through observation, in-depth interviews and document studies, as well as data in the form photos and recordings.Results: The process of solid waste management at the Jogja hospital was carried out by the hospital waste management officer under the direction of the Hospital Environmental Health Installation. Waste Management Officer was a by-contract employee financed by the Hospital. The Incinerator Facility helped the hospital in processing the medical waste and it was also a source income for the hospital since many other parties (private hospitals, general practitioners, private maternity clinic, and midwives) process their waste in the hospital?s incinerator. The monitoring of the air quality, toxic gas and ashes emissions was carried out by the Board of Environmental Health and Contagious Disease Control (BBTKL-PPM) in Yogyakarta. Disposal of ash from burning in place in WWTP Hospital Yogyakarta. Conclusion: Hospital Policies Jogja by performing the contract system to facilitate the supervision of officers. The contract system makes the process of solid waste management to be more effective, because if the officer did a fatal mistake it can be terminated at any time by agreement is a contract. Keywords: Management, Treatment, Solid Waste, Hospital Yogyakarta